Effect of high intensity interval training and supplementation of omega-3 on serum levels of brain derived neurotrophic factor and resting blood pressure of inactive male students - Sajad Karimipour; Shila Nayebifar; Mahmood Fazel Bakhsheshi (مجله دانشگاه علوم پزشکی گرگان, 2020)
Background and Objective: Researches has shown that exercise and nutrition exercises can have a different effect on serum Brain Derived Neurotrophic Factor (BDNF( levels and resting blood pressure in young people. This study was done to determine the effect of a period of High Intensity Interval Training (HIIT) with omega-3 supplementation on the serum levels of BDNF and resting blood pressure in inactive male students. Methods: In this clinical trail study, 32 non-athlete male students were randomly divided into control, supplements, training and training + supplement. Subjects in supplementary group were received daily (2000 mg) of omega-3 capsules. The training groups were also subjected to HIIT training for 6 weeks. The training + Supplemental group also included a combination of the same training program were associated with omega-3 supplementation. BDNF levels were measured by ELISA method 24 and 48 hours perior the exercise protocol and after the last training session. Blood pressure disturbances were also evaluated at the same time and before blood sampling according to the recommendations of the British Heart Association. Results: The serum levels of BDNF in the group after 6 weeks in the training + supplementation group and the training group increased significantly compared to the pre-test values (P˂0.05). Also, a significant difference between-group training + supplementation group and training, supplementation and control groups were observed (P˂0.05). Systolic and diastolic blood pressures were significantly reduced in training + supplementary, training and supplementation groups compared to pretest values (P˂0.05). A significant reduction in systolic blood pressure in the training + supplementation group was observed compared to supplemental and control groups (P˂0.05). Conclusion: HIIT combined with supplementation with omega-3 supplementation improved the BDNF serum level and reducing resting blood pressure in inactive male students.